Narrative and related spoken language skills—a comparison between German-speaking children who are hard of hearing and children with typical hearing - Hardebeck, Lara; Ruigendijk, Esther; Grandon, Bénédicte; Licandro, Ulla (Frontiers in Communication, 2024)
IntroductionNarrative skills are crucial for academic success and social interaction. To date, few studies have looked at the specific impact of hearing loss on higher-level language skills, like narrative skills, especially in German-speaking children. This study is the first to analyze the narrative skills of German-speaking children who are hard of hearing.MethodSpecifically, we assessed and compared the narrative skills of two groups of school-aged children – children who are hard of hearing (n = 22; Mage = 10;5) and children with typical hearing (n = 28; Mage = 9;0) – at the macro- and microstructural level using a standardized storytelling task. In addition, the relationship between spoken narrative skills, receptive vocabulary, and phonological working memory was investigated to determine which factors best predict oral narrative performance.ResultsChildren who are hard of hearing produced adequate narratives at the macrostructural level, but used less diverse vocabulary than their peers without hearing loss. Furthermore, children who are hard of hearing demonstrated lower receptive vocabulary and phonological working memory skills than children with typical hearing. Receptive vocabulary emerged as the most important factor in predicting narrative skills at the microstructural level.DiscussionThe heterogeneity observed in the narratives of children who are hard of hearing emphasizes the need to investigate additional factors that may influence the development and expression of spoken narrative skills in this group.